Mikrosimulasi Kinerja Simpang Bersinyal Dengan Menggunakan Software Surrogate Safety Assessment Model (SSAM) di Kota Malang (Studi Kasus: Simpang Terusan Sulfat) - Pipit Rusmandani; Enrico Pria Anggana; Agus Sasmito (Rekayasa Sipil, 2020)
One of the effort to improve road safety was to reduce the risk of an accident on the intersection in a lowering manner   traffic that occurs. Based on it writer research efforts to improve safety on the Terusan Sulfat intersection in the city poor conflict with how to handle traffic. Research aims to bring down intersections that handling percent fewer traffic intersection. Methods used in the analysis of the performance of simpang used calculation MKJI and trace things back by software PTV VISSIM 10 Full version and methods to know conflict is by using software SSAM. The next step is to provide alternatives from trouble handling the conflict with changes in a traffic intersection to intersection 2 phase with the turn right first  and the 3 phase after setting that up in select most reducing traffic. Conflict The widening of the road in an effort to balance the smooth and  road safety.Handling alternative intersections that chosen provide arrangement simpang with 3 phase with widening of roads because it reduces the occurrence of 30 percent fewer traffic by 26 % and exceptionally large value of 2 % which means maintain a harmony between the creation of road safety and smooth running of the traffic.